Indoor Public Mask-Wearing Behavior Changes in Response to National, State, and Local COVID-19 Policies. Issue 3 (21st May 2022) - Vest, Joshua R.; Cash-Goldwasser, Shama; Peters Bergquist, Eleanor; Embi, Peter J.; Caine, Virginia; Halverson, Paul K.
Abstract : Objective: To estimate changes in public mask-wearing behavior in response to public health policies during COVID-19. Design: Panel of observed public mask-wearing. Setting: Counts of adult behavior in Marion County, Indiana, between November 15, 2020, and May 31, 2021. Determinants of Interest: (1) Removal of state masking requirement; (2) introduction of the National Strategy for the COVID-19 Response and Pandemic Preparedness; (3) the Centers for Disease Control and Prevention (CDC) recommendation that vaccinated individuals did not need to wear masks in public; and (4) COVID-19 vaccine availability. Outcome: Percent observed with correct mask-wearing. Analyses: Fixed-effects models estimated the association between policies and mask-wearing. Results: Ending Indiana's mask requirement was not associated with changes in correct mask-wearing. The CDC's recommendation was associated with a decrease of 12.3 percentage points in correct mask-wearing (95% CI, −23.47 to −1.05; P = .032). Conclusions: Behavior encouraged by local mask requirements appeared to be resilient to changes in state policy. CDC recommendations appeared influential.